2020
DOI: 10.1002/tox.23011
|View full text |Cite
|
Sign up to set email alerts
|

Kolaviron ameliorates hepatic and renal dysfunction associated with multiwalled carbon nanotubes in rats

Abstract: The increase in the exposure to carbon nanotubes (CNTs) and their incorporation into industrial, electronic, and biomedical products have required several scientific investigations into the toxicity associated with CNTs. Studies have shown that the metabolism and clearance of multiwalled CNTs (MWCNTs) from the body involve biotransformation in the liver and its excretion via the kidney. Since oxidative stress and inflammation underlines the toxicity of MWCNT, we investigated the ameliorative effect of kolaviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The wide application of MWCNTs in various fields has raised enormous concerns regarding their health risks for humans. Although the toxicity of MWCNTs had been investigated by numerous studies, most of literatures explored the influence on the inner organs (such as lung, 28 , 29 liver, kidney, 30 brain 31 or reproductive systems). 32 The eye toxicity of MWCNTs was relatively ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The wide application of MWCNTs in various fields has raised enormous concerns regarding their health risks for humans. Although the toxicity of MWCNTs had been investigated by numerous studies, most of literatures explored the influence on the inner organs (such as lung, 28 , 29 liver, kidney, 30 brain 31 or reproductive systems). 32 The eye toxicity of MWCNTs was relatively ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific levels of proinflammatory markers were also assessed. Urea and creatinine levels were reduced, and myeloperoxidase activity, nitric oxide level, reactive oxygen and nitrogen species, and tumor necrosis factor level in kidneys were increased [ 92 ]. Guzmán-Mendoza et al took pristine, pre, and functionalized carbon nanotubes under investigation.…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…2,3 This unique nanoscale structure offers CNTs superior properties suitable for drug delivery, including high drug loading capacity 4 and excellent cellular uptake. 5 However, concerns have emerged regarding the toxicity of CNTs as numerous toxicological studies have identified that CNTs can elicit a pathogenic response, including hepatotoxicity, 6 inhibition of cytochrome P450s (CYP450s), 7 nephrotoxicity, 8 pulmonary fibrosis 9 and immunotoxicity. 10 Furthermore, CNTs have a similar structure to asbestos fibers, and MWCNT-7 (long, rigid CNT) has been classified as possibly carcinogenic to humans (Group 2B) 11 following studies showing that intraperitoneal injection of MWCNTs caused mesothelioma in rodents.…”
Section: Introductionmentioning
confidence: 99%